Pelvik tip ve çaplarının radyolojik incelemesi ve cinsiyet farklılıklarının değerlendirilmesi. - Üstün R.; Çevik S. N.; Büyükmumcu M.; Karamus N. F.; Balsak .; Yabacı Tak A. (My University, 2024)
Aims: Pelvic morphology can vary by gender, geography and racial factors. This study aimed to measure important pelvic diameters in the Turkish population, determine pelvic type incidence, and find the relationship between genders. Methods: Pelvic radiographs of 153 men and women, aged 18-65, selected randomly, were evaluated with X-ray pelvimetry in our study. Pelvic types were determined using Caldwell classification, and conjugata anatomica, obliqua, transversa, vera and diagonalis were measured with Thoms and William\"s technique. Gender differences were analyzed. Results: In 15.7% of cases android type, in 11.8% anthropoid type, in 33% gynecoid type, and in 39.5% platypelloid type pelvis were found. Platypelloid and gynecoid pelvis types were more common in men, while other types were more common in women. Pelvic diameters in women and men were, respectively, conjugata transversa 13.85±0.92 cm and 14.65±0.89 cm, conjugata anatomica 12.8 (8.34-16.65) cm and 13.55 (8.61-17.73) cm, conjugata vera 14.33 (10.14-17.70) cm and 14.84 (10.43-18.30) cm, conjugata diagonalis 15.94 (11.94-19.61) cm and 16.04 (12-19.39) cm, and conjugata obliqua 11.1 (8.47-13.53) cm and 11.81 (8.98-17.81) cm. Except for conjugata diagonalis (p=0.420), pelvic diameters were significantly larger in women (p<0.05). Conclusions: Knowing the morphometric features of the apertura pelvis superior in the population and identifying differences is important in clinical follow-up. Although our study does not represent the entire population due to its cross-sectional nature, we believe the data will contribute to the literature and help consider differences in pelvic morphology.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Anatomi; Medicine; Health Sciences; Fundamental Medical Sciences; Human Anatomy; Klinik Tıp (Med); Yaşam Bilimleri (Life); Klinik Tıp; Biyoloji ve Biyokimya; Anatomi ve Morfoloji; Tıp Genel & Dahili; Clinical Medicine (Med); Life Sciences (Life); Clinical Medicine; Biology & Biochemistry; Anatomy & Morphology; Medicine General & Internal; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Anatomy; Medicine (miscellaneous); General Medicine